1999
DOI: 10.1007/bf02478904
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of pineal parenchymal tumors: correlation between histopathological features, proliferative potential, and prognosis

Abstract: This study describes the clinicopathologic features of 13 cases with pineal parenchymal tumors. Based on the histopathologic findings, especially the extent of atypia and pineocytic differentiation as determined by Bodian's staining, we classified these tumors into pineocytomas (4), pineocytomas with anaplasia (4) and pineoblastomas (5). All the cases with pineocytoma and pineocytoma with anaplasia were adults, and all the cases with pineoblastoma were younger children. One patient with pineocytoma died of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 20 publications
(1 reference statement)
3
28
1
Order By: Relevance
“…The proliferative potential of PCs has been reported to be low compared to that of PBs. [20][21][22] In the case reported here, the MIB-1 index was higher than those reported for PCs in the literature, which is often around 1%; 21 however, this labeling index was reported to reach a maximum of 4% in a large series of PPTs. 20 The utility of this labeling index in distinguishing the different grades of PPT has not yet been validated and it has been reported that the MIB-1 index is not predictive of recurrence potential in PCs.…”
Section: Discussioncontrasting
confidence: 76%
“…The proliferative potential of PCs has been reported to be low compared to that of PBs. [20][21][22] In the case reported here, the MIB-1 index was higher than those reported for PCs in the literature, which is often around 1%; 21 however, this labeling index was reported to reach a maximum of 4% in a large series of PPTs. 20 The utility of this labeling index in distinguishing the different grades of PPT has not yet been validated and it has been reported that the MIB-1 index is not predictive of recurrence potential in PCs.…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, these patients are managed in different ways in different institutions complicating the interpretation of published literature. Adult PBL patients have been treated with localized radiotherapy to the pineal region [21,25,26,35] or subjected to radical resection, radiotherapy, and chemotherapy [3,31]. Previous series have been published without central histological review and diagnostic confirmation only undertaken by the pathologist at the initial institution to which the patient presented [1,11,16].…”
Section: Introductionmentioning
confidence: 98%
“…In the former case, tumor cells morphologically exhibit malignant features, but the biological and clinical behavior is similar to benign pineocytoma. 5 In contrast, mixed pineal parenchymal tumors content pineoblasomatous area of high malignant potential, and are prone to metastasis than pineal parenchymal tumor baring intermediate histological features of pineocytoma and pineoblastoma (PPTID in a narrow sense), 6 therefore, PPTID should be distinguished from mixed pineocytoma and pineoblastoma. In the present case, typical elements of pineoblastoma were not observed in both cytology and histology, but we could not completely deny the possibility of mixed parenchyma tumor.…”
Section: Discussionmentioning
confidence: 95%
“…9,10 In the case with immunoreactivity for NFP and a mitotic count less than 6 per 10 high-power fields, more favorable outcome can be expected: The WHO grade II and III cases showed about 80 and 40% of 5-year follow-up, respectively. Tsumanuma et al reported an important investigation that MIB-1 labeling index might be used for differential diagnosis between pineoblastoma (mean 15.7%) and pineocytoma (mean 3.9%), 5 however, in pineal parenchyma tumors, biological behavior is more closely correlated to the spectrum of differentiation than to proliferative activity. 6,11 Further clinicopathological studies are required to conclude the correlation between MIB-1 labeling index and prognosis in PPTID.…”
Section: Discussionmentioning
confidence: 96%